Ethnographic Study at a Music Library Found Students Prefer Short Stopovers and Longer Solitary Study - Daniel, Dominique (Evidence Based Library and Information Practice, 2014)
Objective – To identify patterns of patron behaviour in the library in order to improve space utilization. Design – Ethnographic data-gathering, including observations and a qualitative survey. Setting – Music library of a large public university. Subjects – Library patrons, primarily music students but also music faculty, other students and faculty, and regional music professionals and amateurs. Methods – In the exploratory phase, complete (i.e., incognito) participant observers recorded patron characteristics and behaviours in four zones of the library (the technology lab, the stacks, the reference area, and study carrels). They conducted a series of five-minute-long visual sweeps of these zones at five-minute intervals. Observers were not given any checklist, but were told to record anything they saw regarding the personal characteristics, behaviours, and activities of patrons. The data collected resulted in what the investigators called “flip books” (a series of images recorded in close succession, which, when flipped, could give the illusion of movement). The data was analyzed using the grounded theory approach, a qualitative method to identify recurring themes on space use. A statistical analysis based on these themes was then conducted. In the second, explanatory phase, observers conducted new “sweeps,” or observations of the same library zones, this time using checklists to indicate the occurrence of specific activities identified in the first phase (solo vs. group activity, social interaction vs. study discussion, and use of technology). In addition, observers recorded patron entry and exit on “time cards,” and had all exiting patrons answer five brief questions about the types and volume of activities they had conducted in the various zones of the library. Main Results – The vast majority of the patrons were students. Most (at least three-quarters) engaged in solitary activity, and a large majority used electronic technology. According to data from the flip books, 44% engaged in multitasking, which was therefore significant but not preferred. It was more likely to occur when electronic technology was involved. Patrons were most likely to be present in the library for less than 5 minutes or more than 20 minutes. Patrons who stayed in the library for only a short time were more likely to engage in leisure activities than those who stayed longer, but leisure activities overall were as prevalent as study time. The technology lab and the reference area were the most popular zones. Users stayed in the technology lab and stacks for short times only, whereas the reference area and carrels were favored for long visits. Users engaged in multitasking mostly in the carrels and reference area. Conclusion – The patrons’ preference for solitary study is at odds with academic libraries’ current interest in collaborative learning spaces, but can be explained by the specific nature of music studies (artistic creation is a solitary activity), and is in line with previous ethnographic studies of public libraries. Music students presumably use the technology labs for short visits between classes. They favor the study carrels for longer stays where they can multitask, using their own laptops and iPods. These findings can be used to help redesign the library. Design recommendations include placing the technology lab by the entrance to enable quick coming and going, increasing the number of carrels, placing them in quiet parts of the library, and equipping them with electrical outlets.